2021
DOI: 10.1029/2021gl096169
|View full text |Cite
|
Sign up to set email alerts
|

Subion‐Scale Flux Rope Nested Inside Ion‐Scale Flux Rope in Earth's Magnetotail

Abstract: Magnetic flux ropes (MFRs)—transient magnetic structures widely observed in Earth's magnetosphere—play crucial roles in particle acceleration and energy dissipation. MFRs above ion scale have been well studied, while MFRs at subion scales and their coupling with larger‐scale ropes still remains not well understood. In this paper, we present the first observation of a subion‐scale MFR nested in an ion‐scale MFR, using high‐resolution data from the magnetospheric multiscale (MMS) mission. We find that the subion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Ion energy flux (0.1-100 keV) (Figure 4(d)) dramatically increases by 2-4 orders of magnitude inside the MFR. The transient trends resemble the typical characteristics of an MFR often observed or simulated in the magnetotail (Lin et al 2014;Lu et al 2019;He et al 2021;Zhang et al 2021). That is, the evolution of flux ropes in the magnetotail can lead to ion acceleration.…”
Section: Ion Accelerationsupporting
confidence: 62%
See 1 more Smart Citation
“…Ion energy flux (0.1-100 keV) (Figure 4(d)) dramatically increases by 2-4 orders of magnitude inside the MFR. The transient trends resemble the typical characteristics of an MFR often observed or simulated in the magnetotail (Lin et al 2014;Lu et al 2019;He et al 2021;Zhang et al 2021). That is, the evolution of flux ropes in the magnetotail can lead to ion acceleration.…”
Section: Ion Accelerationsupporting
confidence: 62%
“…Such MFRs at magnetopause have four possible topologies inferred from electron pitch-angle distributions (Pu et al 2013), and often consist of two interlinked flux tubes (Hwang et al 2021). He et al (2021) found a subion-scale MFR nested within an ion-scale MFR in magnetotail, where their axes are perpendicular to each other. Chen et al (2021) reported an electron-scale MFR in the electron diffusion region and reconstructed its 3D magnetic field topology.…”
Section: Introductionmentioning
confidence: 92%
“…In this sense, it is quite reasonable for the FOTE method to find a twisted structure without the bipolar signature in the time‐serious spacecraft data. It's clearly found that the topology of this twisted magnetic structure is not the reconnection current sheet, which has an “X‐shape” topology (Fu et al., 2016; Fu, Wang, et al., 2020; Z. Wang et al., 2020, 2022; Zhang et al., 2023), and O‐lines, which is consisted of spiral magnetic field lines (Eastwood et al., 2016; He et al., 2021; Hwang et al., 2021; Øieroset et al., 2016; R. Wang et al., 2016; Z. Wang, Vaivads, Fu, Cao, Lindberg, et al., 2023; Z. Wang, Vaivads, Fu, Cao, & Liu, 2023), including magnetic flux ropes and magnetic islands. And it's also certainly not a nonlinear structure such like a magnetic hole (Liu, Fu, Olshevsky, et al., 2019; Liu et al., 2020; Yu et al., 2023).…”
Section: Observationmentioning
confidence: 99%
“…Multipoint spacecraft observations showed that the magnetic structures associated with the earthward and tailward bulk flows can be formed at ion and sub-ion kinetic scales and/or have very thin fronts/boundaries with a characteristic thickness of the order of ion gyroradius or less (Sergeev et al 2009;Balikhin et al 2014;Huang et al 2016;Grigorenko et al 2018;He et al 2021). These structures can be the sites of strong energy dissipation (e.g., Drake et al 2006;Fu et al 2006;Oka et al 2010;Huang et al 2019), which affects the particle velocity distribution functions and causes the generation of various types of electromagnetic and electrostatic wave modes (e.g., Zhang et al 1999;Le Contel et al 2009;Tenerani et al 2013;Fujimoto 2014Fujimoto , 2017Zhang & Angelopoulos 2014;Grigorenko et al 2016;Huang et al 2016;Wang et al 2016;Guo et al 2021;Pickett 2021).…”
Section: Introductionmentioning
confidence: 99%